818 A Ghost from the Past: Unmasked Insomnia Affecting Hypoglossal Nerve Stimulation Therapy Adherence. (3rd May 2021) - Stuewe, Elena; Grover, Aarti; Ostrow, Peter; Schumaker, Greg; Oster, Joel; Zacharias, Rajesh
Abstract: Introduction: Hypoglossal nerve stimulation (HNS) is an efficacious option for treating moderate to severe obstructive sleep apnea (OSA). However, there is sparse evidence regarding tolerance and adherence to HNS therapy in patients with a diagnosis of insomnia. Report of case(s): A 57-year-old man with well-controlled depression presented for evaluation for HNS therapy. He had been diagnosed with moderate OSA with an apnea-hypopnea index of 22/hour, intolerant of continuous positive airway pressure and mandibular advancement device. He underwent uvulopalatopharyngoplasty without significant improvement. At the time of initial evaluation, he denied history of insomnia and prior sleep aid use. He subsequently underwent successful HNS device implantation and activation. One week after HNS initiation, the patient reported new symptoms of significant difficulty with sleep onset and inability to fall back asleep, which was worse than his untreated OSA symptoms. Device interrogation did not reveal any hardware problems. Adjustments to start delay, pause time and device configuration with awake endoscopy did not improve tolerance. Subsequently, the patient disclosed a remote history of insomnia, which was treated with multiple hypnotics in addition to cognitive-behavioral therapy for insomnia (CBTi) and had resolved. He was diagnosed with recurrent chronic insomnia, for which eszopiclone was initiated without significant improvement. He eventually agreed to CBTi, with partial improvement in device tolerance and improvement in insomnia symptoms. Conclusion: This case highlights that HNS therapy adherence can be affected by prior history of, or a current diagnosis of insomnia. Our patient had a predisposition for insomnia that was well controlled prior to HNS therapy initiation. The onset of recurrent insomnia with HNS activation suggests that HNS was a precipitating factor for his now chronic insomnia. Although there is insufficient evidence to suggest whether history of insomnia should affect the decision to initiate HNS therapy, this case illustrates the importance of screening for insomnia at pre-implant evaluation. Our center is now routinely screening for a history of insomnia to identify patients who may benefit from treatment prior to HNS implantation. Larger studies are needed to explore a possible relationship between insomnia and HNS adherence. Support (if any):